The High Prevalence of Knee Osteoarthritis in North China Population: The Handan Osteoarthritis Study - Xie Zhi-Tao, Wang Shen, Zhang Yong-Tao, Tian Zai-Jie, Ma Zhi-Lin, Liu Bo-Yu; Jing, Niu (International Journal of Innovative Research in Medical Science, 2017)
Objective: To investigate the prevalence of Handan city urban and rural elderly population in osteoarthritis and to discusses its characteristics and risk factors for disease Methods: One neighborhood committees and two suburban counties are randomly selected. To draw to the r (village) committee that all residents over the age of 45 epidemiological investigation, questionnaire survey knee joint disease situation, college visits and physical examination and X-ray fluoroscopy. Results: The total prevalence rate of knee osteoarthritis is 9.1%, the prevalence of 9.6% rural residents 9.6% of urban residents; Unreasonable 11.8% 5.9% of men women, gender, age, body mass index(BMI), urban and rural residents is not reasonable way of life and work associated with knee osteoarthritis. Conclusion: Gender, age, body mass index, urban and way of life and work of rural residents are risk factors of knee osteoarthritis, should actively intervene to reduce the pathogenic effects of such factors.